Application of Quantitative Measures for Analysing Aircraft Handling Qualities - Hebbar, Archana; Pashilkar, Abhay A. (Defence Science Journal, 2016)
The ease and precision with which pilot is able to handle the designated task determines the aircraft’s handling qualities. Accordingly, the most common methodology for determining aircraft’s handling qualities is through pilot opinions or through questionnaires. These subjective means of analysis is not reliable as the sole source of judgments. Quantitative metrics to analyse the task difficulty based on pilot’s performance, supplemented with subjective decision, can provide better insight into pilot workload levels and in turn the aircraft’s handling qualities. The application of few objective performance measurement techniques to flight data of a high performance fighter aircraft is discussed. Pilot/aircraft’s performance under different configurations is analysed. Analysis results show that pilots usually tend to give more priority to pitch axis in case of dual axis tracking task. And pilots are therefore more aggressive in accomplishing pitch axis tracking task than in roll. Workload assessments were also performed by comparing the results of single axis tracking experiments conducted using a high fidelity flight simulator with the flight data. It is seen that pilot’s aggressiveness levels in controlling the roll control inceptor is significantly less, with improved tracking accuracy when exercised as the primary task.